2021
DOI: 10.1021/acs.jpcb.1c07864
|View full text |Cite
|
Sign up to set email alerts
|

Cis-Isomers of Photosensitive Cationic Azobenzene Surfactants in DNA Solutions at Different NaCl Concentrations: Experiment and Modeling

Abstract: The DNA interaction with cis-isomers of photosensitive azobenzenecontaining surfactants was studied by both experimental methods and computer simulation. It was shown that before the organization of micelles, such surfactants in the cis-conformation form associates of only a single type with a disordered orientation of molecules. In contrast, for trans-isomers, there exist two types of associates with headto-head or head-to-tail orientations of molecules in dependence on salt concentration in a solution. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Later, the surfactant cations began to aggregate with each other in solution as well as to bind to DNA phosphates and to form aggregates on DNA. The structure of the aggregates for the cis- and trans-surfactants has been studied in detail earlier. , Obviously, small trivalent cations have an advantage over the monovalent surfactant cations in binding to DNA phosphates.…”
Section: Results Of Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…Later, the surfactant cations began to aggregate with each other in solution as well as to bind to DNA phosphates and to form aggregates on DNA. The structure of the aggregates for the cis- and trans-surfactants has been studied in detail earlier. , Obviously, small trivalent cations have an advantage over the monovalent surfactant cations in binding to DNA phosphates.…”
Section: Results Of Modelingmentioning
confidence: 99%
“…The micelle size weakly depends on the salt concentration. It was shown that for cis-isomers the micelle size is smaller than that for trans-isomers, and the ionic strength of the solution influences it …”
Section: Results Of Experiments and Discussionmentioning
confidence: 99%
See 3 more Smart Citations